To disentangle strong resonant Auger decay lines after the O1s→3σu*excitation in O2 molecules. Issue 14 (January 2020) - Ding, B; Xu, W Q; Nicolas, C; Song, S; Jiang, Y; Patanen, M; Nandi, S; Xiao, Z; Miron, C; Liu, X J
Synopsis: Atomic features may appear in the Auger electron spectra after an electron is excited from a core orbital to an antibonding orbital in molecules, as a result of complex competitions among electron and nuclear motions. Relatively weak atomic features were widely discussed in spectator Auger decay processes on top of O 1 s → 3 σ u * excitation in O2 molecules. Thee strong Auger decay processes are heavily-overlapped in the electron spectrum and not discussed up to now. Here, using multi-particle coincidence setup, we separate these Auger decay processes for the first time.